MENINGKATKAN KEMAMPUAN BERBAHASA MELALUI MODEL PEMBELAJARAN AUDIO-VISUAL PADA ANAK KELOMPOK USIA 4-5 TAHUN - Ikma Zakiah; Dedah Jumiatin (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2021)
Having language skills in terms of expressing can encourage children to be brave enough to face life's problems naturally (not to feel pressured) and full of responsibility, and to be able to express their opinions proactively and creatively to deal with problems. The formulation of the problem in this study is whether the audio-visual learning model can improve the language skills of children aged 4-5 years. The aim is to determine the escalation of language skills of children aged 4-5 years through audio-visual media. The form of the research uses a classroom action research design. The research subjects were 12 children, namely 5 boys and 7 children at KOBER Al-Falah. Data collection techniques are in the form of observation and documentation. After the data was obtained, it was analyzed and reflected using the percentage technique. Research on the escalation of language skills can be seen from the escalation indicator of student learning outcomes which always increases from cycle I (33.3%), cycle II (58.3%), and cycle III (83.3%). The escalation of indicators in this study can be seen when the child dares to express his opinion, recounts something that he has / that he has just seen and knows, as well as the courage to express his opinion.Memiliki kemampuan bahasa dalam hal mengungkapkan dapat mendorong anak untuk berani menghadapi persoalan hidup dengan wajar (tidak merasa tertekan) dan penuh tanggung jawab, serta mampu mengutarakan pendapatnya secara proaktif dan kreatif untuk menghadapi persoalan..Rumusan masalah penelitian ini adalah Apakah model pembelajaran audio visual dapat meningkatkan kemampuan berbahasa anak usia 4-5 tahun. Tujuannya adalah untuk mengetahui eskalasikemampuan berbahasa anak usia 4-5 tahun melalui media audio visual. Bentuk penelitiannya menggunakan desain penelitian tindakan kelas. Subjek penelitiannya 12 anak yaitu 5 orang anak laki-laki dan 7 orang anakdi KOBER Al-Falah. Teknik pengumpulan data berupa observasi, sertadokumentasi. Setelah data diperoleh kemudian dianalisis dan direfleksi menggunakan teknik persentase. Penelitian eskalasikemampuan berbahasa dapat dilihat dari indikator eskalasihasil akhir belajar siswa yang selalu meningkat dari siklus I (33,3%), siklus ke II (58,3%), dan siklus ke III (83,3%). Eskalasi indikator dalam penelitian ini dapat dilihat saat anak berani mengungkapkan pendapatnya, menceritakan kembali sesuatu yang ia dapat/ yang baru ia lihat dan ia ketahui, serta keberanian dalam ha berpendapat.